In the world of Dolly, when does a human embryo acquire respect?. Issue 4 (30th March 2005) - Cameron, C; Williamson, R
Abstract : For most of the 20th century, it was possible to regard fertilisation as the identifiable point when life begins, because this moment could be defined unequivocally and was thought to be the single most essential biological step in the establishment of a new human entity. Since the successful reproductive cloning of Dolly and other mammals, it is clear that any human cell has the potential to supply the full genome of an embryo, and hence a person, without going through fertilisation. At what point in time do such embryos acquire the respect accorded to human beings? The authors argue that the time of implantation is the most useful point at which the potential and the intention to create a new person are translated into reality, because from that point a new life develops. Implantation differentiates a somatic cell in culture (which is not due respect) from a human entity that has acquired its own identity and developmental potential. The authors examine the value of quickening or viability as alternative developmental stages in the process of acquiring respect for the Dolly embryo.